DISCRIMINATION SUFFERED BY NYAI ONTOSOROH IN PRAMOEDYA ANANTA TOERâ€™S THIS EARTH OF MANKIND - Favianus Kurniawan; Rr. Arielia Yustisiana (Universitas Katolik Widya Mandala Surabaya, 2021)
The research aimed to discuss discrimination in Pramoedya Ananta Toer â€œThisEarth of Mankindâ€. The objectives of the research were to describe the NyaiOntosoroh characterization. After described the Nyai Ontosoroh characterizationin the novel, would be kinds of discrimination that Nyai character suffered. Thetheories that used in this study were characterization, post-colonialism, setting,and discrimination. Theory of characterization is useful for knowing thedevelopment of characters in literary works such as novel. Theory of postcolonialismused to understand the civilization and improvement serves as theimpact experienced by the third world societies in the past, present, even in thefuture. The setting theory was to describe the society that lived in the specificplace and time means post-colonialism era. The discrimination theory was toanalysis the events related to discrimination and the form of discrimination itselfthat exists in literary works such as novels. The Innocence theory was to supporttheory of symbol Innocence. The technique of data collecting was libraryresearch, while the method of this research was descriptive. There were fourapproaches used in the study. They were feminist, moral, psychological andsociological approaches. The result of this research showed about discriminationthat suffered Indonesian people because of the Dutch related to the novel ThisEarth of Mankind by Pramoedya Ananta Toer. The statement of problems in thisresearch divide into two. First problem as followed a well- educated woman, astraight forward woman, brave and wise woman, responsible woman, respectedwoman, a persevered woman, realistic and persistent woman, and a competitivewoman. The second problem is as followed unable to fill the gabs, judge assinner, betrayed by her parents, treated like slaves, judged as being a badinfluence, accused as a murderer, accused as a thief, and treated unfairly legally.Â Â Keywords: Discrimination, Characterization, Suffering